The Modulatory Role of Heme Oxygenase on Subpressor Angiotensin II-Induced Hypertension and Renal Injury - Kiran Chandrashekar; Arnaldo Lopez-Ruiz; Ramiro Juncos; Karl Nath; David E. Stec; Trinity Vera; Ruisheng Liu; Luis A. Juncos (International Journal of Hypertension)
Angiotensin II (AngII) causes hypertension (HTN) and promotes renal injury while simultaneously inducing reno-protective enzymes like heme oxygenase-1 (HO-1). We examined the modulatory role of HO on sub-pressor angiotensin II (SP-AngII) induced renal inflammation and injury. We first tested whether the SP-AngII-induced renal dysfunction, inflammation and injury are exacerbated by either preventing (chronic HO-1 inhibition) or reversing (late HO-1 inhibition) SP-AngII-induced HO (using tin protoporphyrin; SnPP). We next examined whether additional chronic or late induction of SP-AngII-induced HO (using cobalt protoporphyrin; CoPP), prevents or ameliorates renal damage. We found that neither chronic nor late SnPP altered blood pressure. Chronic SnPP worsened SP-AngII-induced renal dysfunction, inflammation, injury and fibrosis, whereas late SnPP worsened renal dysfunction but not inflammation. Chronic CoPP prevented HTN, renal dysfunction, inflammation and fibrosis, but surprisingly, not the NGAL levels (renal injury marker). Late CoPP did not significantly alter SP-AngII-induced HTN, renal inflammation or injury, but improved renal function. Thus, we conclude (a) endogenous HO may be an essential determining factor in SP-AngII induced renal inflammation, injury and fibrosis, (b) part of HO’s renoprotection may be independent of blood pressure changes; and (c) further induction of HO-1 protects against renal injury, suggesting a possible therapeutic target.